2023
DOI: 10.3389/fpsyg.2023.1139427
|View full text |Cite
|
Sign up to set email alerts
|

Hopium or empowering hope? A meta-analysis of hope and climate engagement

Nathaniel Geiger,
Timothy Dwyer,
Janet K. Swim

Abstract: Researchers are increasingly examining whether hope can motivate action on climate change, or conversely, whether it might demotivate such action. We present a meta-analysis (k = 46) of quantitative studies examining the relationships between measures and manipulations of hope with climate engagement. On average, measured hope was associated with greater climate engagement (r = 0.18); however, this effect differed based on the target of hope. Hope regarding the possibility of respondents taking action was part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…A person who does not feel any hope about the future of climate change and who believes humanity is doomed is unlikely to be concerned about how (doomed) future generations might remember them. While previous work did not find a connection between hope about societal efficacy for addressing climate change (Geiger et al, 2023), the connection between that kind of hope and legacy motivation is unclear. One aim of this work is to understand whether legacy motives relate to feelings of constructive hope or hope based in denial and how hope relates to the ways people respond to climate change threat information and intentions to adopt proenvironmental behaviors (Study 2).…”
Section: Legacy and Hopementioning
confidence: 77%
See 1 more Smart Citation
“…A person who does not feel any hope about the future of climate change and who believes humanity is doomed is unlikely to be concerned about how (doomed) future generations might remember them. While previous work did not find a connection between hope about societal efficacy for addressing climate change (Geiger et al, 2023), the connection between that kind of hope and legacy motivation is unclear. One aim of this work is to understand whether legacy motives relate to feelings of constructive hope or hope based in denial and how hope relates to the ways people respond to climate change threat information and intentions to adopt proenvironmental behaviors (Study 2).…”
Section: Legacy and Hopementioning
confidence: 77%
“…In one study, promoting feelings of hopefulness decreased a sense of threat and willingness to sacrifice for climate change (Bilandzic et al, 2017), but in other samples participants who expressed or experienced hope about climate change rooted in trust in others, positive-reappraisals, feelings of determination, and perceptions that barriers can be overcome ('constructive hope') were also more likely to be proenvironmental in their attitudes and behaviors (Ojala, 2012;2023). One meta-analysis (Geiger et al, 2023) found that certain kinds of hope (particularly hope that one would be able to engage in effective climate action) relate to greater climate engagement, but hope based in denial related to less engagement. An alternative view of the relationship between hope and legacy is that a sense of hope may be necessary for one to become concerned about one's legacy.…”
Section: Legacy and Hopementioning
confidence: 99%
“…Research has shown that hope can be a powerful motivator. A meta-analysis found that those who felt hopeful about getting involved with taking action on climate change were much more willing to take action and support policy to address the issue [54]. In contrast, feeling hopeful about climate change more generally or society's ability to address it (rather than hope about personally getting involved) was not as strongly associated with action or policy support.…”
Section: Experts Agreed That Catalysts Are Needed To Implement Climat...mentioning
confidence: 99%
“…That is, collective climate action may be perceived as something to perhaps be pursued (hypothetical distance) in the future (temporal distance), elsewhere (spatial distance), by others unlike oneself (social distance) (Table 1). Attention to the psychological distance of collective climate action could help to "transform the notions of collective action and community into something more concrete and tangible" 25 , thereby generating "empowering hope" rooted in plans to personally take action 26 .…”
Section: Psychological Distance From Collective Climate Actionmentioning
confidence: 99%